FTIR spectroscopy combined with chemometrics for analysis of lard adulteration in some vegetable oils - Abdul Rohman,; Che Man, Yaakob; Hashim, Puziah; Ismail, Amin (Taylor & Francis, 2011)
This study was aimed to develop a fast technique of Fourier transform infrared (FTIR) spectroscopy for detection and quantification of lard adulteration in some vegetable oils, namely canola oil (Ca‒O), corn oil (CO), extra virgin olive oil (EVOO), soybean oil (SO), and sunflower oil (SFO). The FTIR spectra associated with Ca‒O, CO, EVOO, SO, and SFO as well as their blends with lard were scanned, interpreted, and identified. The chemometrics of partial least square (PLS) and discriminant analysis (DA) at fingerprint regions of 1500–1000 cm−1 was used for quantifying and classifying of lard in the mixture with vegetable oils, respectively. PLS calibration can be successfully used for quantification of lard in the mixture with vegetable oils, either using normal spectra or its first derivatives. Furthermore, DA based on Mahalanobis distance can classify lard in vegetable oils. El objetivo de este estudio fue desarrollar una técnica rápida de espectroscopia de infrarrojos por transformada Fourier (FTIR) para la detección y cuantificación de adulteración con grasa de cerdo de algunos aceites vegetales, principalmente aceite de colza (Ca‒o), aceite de maíz (CO), aceite de oliva virgen extra (EVOO), aceite de soja (SO) y aceite de girasol (SFO). El espectrograma FTIR asociado con Ca‒O, CO, EVOO, SO y SFO, así como sus mezclas con grasa de cerdo, fueron escaneadas, interpretadas e identificadas. El análisis quimiométrico de mínimos cuadrados parciales (PLS) y análisis discriminantes (DA) en la región de 1500–1000 cm−1 se usaron para cuantificar y clasificar la grasa de cerdo en la mezcla con aceites vegetales, respectivamente. La calibración PLS puede ser usada satisfactoriamente para la cuantificación de grasa de cerdo en la mezcla con aceites vegetales, bien usando un espectro normal o sus primeras derivadas. Además, DA basados en la distancia Mahalanobis pueden clasificar la grasa de cerdo en aceites vegetales.